Foamy copper composite three-dimensional current collector, preparation method and application thereof, composite lithium metal negative electrode, lithium battery and electric equipment
The FeF3 solution immerses the foam copper, and generates a copper oxide coating, which solves the problem of battery performance degradation caused by lithium dendrites, and achieves the stable Coulomb efficiency and long life of lithium batteries.
Patent Information
- Application Number
- CN202311181879.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
The growth of lithium dendrites in existing lithium batteries leads to damage to the SEI film, low Coulomb efficiency, loss of battery capacity, and may cause short circuits, seriously affecting the application of lithium metal batteries.
FeF3 solution is used to immerse the foam copper foam, and an oxide copper oxide coating is formed by slow oxidation to form a foam copper composite three-dimensional current collector, and the oxidation reaction is controlled to maintain the flexibility and integrity of the foam copper foam.
The uniform deposition of lithium metal is achieved, the growth of lithium dendrites is inhibited, the efficiency of Coulombs is stabilized, and the service life of lithium batteries is extended.
Smart Images

Figure CN119627116A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium battery current collectors, and in particular to a foam copper composite three-dimensional current collector and a preparation method and application thereof, a composite lithium metal negative electrode, a lithium battery and electrical equipment. Background Art
[0002] So far, the commercial use of rechargeable lithium metal batteries is still very limited, one of the reasons is dendrites. The formation of lithium dendrites is a technical problem that the lithium battery industry cannot avoid. As long as the lithium-ion battery is charged and discharged, lithium dendrites will be formed when the lithium ions are reduced. The growth of lithium dendrites will continuously destroy the generated SEI film, expose more specific surface area, and continuously consume electrolyte, resulting in low Coulomb efficiency and continuous loss of battery capacity. After a long period of accumulation, when the lithium dendrites grow to a certain length, they will puncture the diaphragm and cause a short circuit inside the lithium-ion battery. Once a short circuit occurs inside the lithium-ion battery, the lithium-ion battery will be scrapped at the least, and in severe cases, it will threaten life safety. The lithium dendrite problem has seriously inhibited the practical application of lithium metal batteries.
[0003] Therefore, in order to inhibit the growth of lithium dendrites in the lithium metal negative electrode, enable lithium ions to be deposited in an orderly manner, stabilize the SEI film on the surface of lithium metal, and make lithium metal batteries safe and have a long service life, one of the methods frequently used in this field is current collector design. However, the current traditional negative electrode current collector uses FeCl3 to oxidize commercial copper foam, but FeCl3 has strong oxidizing properties. When reacting with copper foam, the reaction is often difficult to control, resulting in severe oxidation of the copper foam and severe structural damage. In addition, the original flexibility of the copper foam is lost and it becomes brittle. When the battery is packaged, the brittle copper foam can easily pierce the diaphragm, making the battery inoperable. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem of lithium battery dendrites in the prior art, and to provide a foam copper composite three-dimensional current collector and its preparation method and application, a composite lithium metal negative electrode, a lithium battery and an electrical device. The obtained foam copper composite three-dimensional current collector is wrapped with cuprous oxide and has a stable coulombic efficiency.
[0005] In order to achieve the above objectives, the first aspect of the present invention provides a method for preparing a foam copper composite three-dimensional current collector, wherein the foam copper is immersed in a FeF3 solution to obtain a foam copper composite three-dimensional current collector having a surface coated with a cuprous oxide layer.
[0006] The second aspect of the present invention provides a foam copper composite three-dimensional current collector prepared by the preparation method of the first aspect of the present invention.
[0007] The third aspect of the present invention provides an application of the foam copper composite three-dimensional current collector of the present invention in a lithium battery.
[0008] A fourth aspect of the present invention provides a composite lithium metal negative electrode, wherein the composite lithium metal negative electrode comprises the above-mentioned foam copper composite three-dimensional current collector.
[0009] A fifth aspect of the present invention provides a lithium battery, wherein the lithium battery comprises the above-mentioned composite lithium metal negative electrode.
[0010] A sixth aspect of the present invention provides an electrical device, wherein the electrical device includes the above-mentioned lithium battery.
[0011] Through the above technical solution, when the copper foam reacts with the FeF3 supersaturated solution, Fe 3+ Slowly oxidize the foam copper to form cuprous oxide particles on its surface. When the Fe 3+ When the concentration is low, FeF3 continuously releases Fe 3+ , so that the oxidation reaction proceeds continuously and orderly. Compared with the traditional FeCl3 oxidant, FeF3 as an oxidant has a mild reaction and is easy to control. The copper foam can maintain its original flexibility and integrity. The surface of the copper foam can be coated with a dense and uniform layer of cuprous oxide, and the thickness of the coating layer can be controlled by the reaction temperature and time. The dense and uniform cuprous oxide coating enables the copper foam to achieve a stable and high coulombic efficiency when used as a lithium metal current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Optical photographs and SEM photographs of products of copper foam (CF) and saturated FeF3 solution at 60° C. prepared in Examples 1-4 of the present invention reacted at different temperatures for 10 hours;
[0013] Figure 2 This is a comparison chart of the coulombic efficiency of the copper foam composite three-dimensional current collector prepared in Example 9 of the present invention and commercial copper foam;
[0014] Figure 3 This is a comparison chart of the cycle performance of the composite lithium metal negative electrode prepared in Example 9 of the present invention and a full battery assembled with commercial lithium and NCM-811. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] A first aspect of the present invention provides a method for preparing a foam copper composite three-dimensional current collector, wherein the foam copper is immersed in a FeF3 solution to obtain a foam copper composite three-dimensional current collector having a surface coated with a cuprous oxide layer.
[0017] When the FeF3 solution is unsaturated, the Fe 3+ Too little is not conducive to promoting the reaction that occurs during immersion.
[0018] In some embodiments of the present invention, preferably, the FeF3 solution is a saturated FeF3 solution; preferably, the saturated FeF3 solution is a saturated solution at 55-80°C, preferably a saturated solution at 55-65°C. If the temperature of the saturated FeF3 solution is too high (higher than 80°C), FeF3 may decompose, and if the temperature is too low (lower than 55°C), there is too little FeF3 in the solution, which is not conducive to promoting the reaction. The temperature of the saturated FeF3 solution can be any value within the numerical range of any two of 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C, and can also be any value within the numerical range of any two of 55°C, 58°C, 60°C, 62°C, and 65°C.
[0019] In some embodiments of the present invention, preferably, the immersion process comprises: reacting at a temperature of 60-100°C for 8-12 hours, cooling to room temperature, taking out the copper foam, washing and drying, and obtaining a copper foam composite three-dimensional current collector with a surface coated with a cuprous oxide layer; preferably, the immersion process comprises: reacting at a temperature of 70-90°C for 8-10 hours. The immersion temperature can be any value within the range of any two values of 60°C, 70°C, 80°C, 90°C, and 100°C, and the immersion temperature can also be any value within the range of any two values of 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, and 90°C; the reaction time can be any value within the range of any two values of 8h, 9h, 10h, 11h, and 12h, and can also be any value within the range of any two values of 8h, 8.5h, 9h, 9.5h, and 10h.
[0020] In some embodiments of the present invention, preferably, the preparation method further comprises: before the reaction, soaking the copper foam in dilute hydrochloric acid to remove the oxide layer on its surface, wherein the concentration of the dilute hydrochloric acid is 0.05-0.2 mol / L, and the soaking time is not less than 6 hours. The concentration of the dilute hydrochloric acid can be any value within the range of any two values of 0.05 mol / L, 0.1 mol / L, 0.15 / mol / L, and 0.2 mol / L. The soaking time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc., and can also be any value within the range of any two values thereof.
[0021] The second aspect of the present invention provides a foam copper composite three-dimensional current collector prepared by the preparation method of the first aspect of the present invention.
[0022] The copper foam composite three-dimensional current collector prepared by the method provided by the present invention has cuprous oxide coated on the surface of the copper foam as a substrate densely and evenly. When the current collector is used as a lithium metal current collector in a lithium battery, it can well achieve uniform deposition of lithium metal, inhibit the growth of lithium dendrites, and achieve stable and high coulombic efficiency.
[0023] In some embodiments of the present invention, preferably, the copper foam composite three-dimensional current collector comprises copper foam and a cuprous oxide layer wrapped on the surface of the copper foam, wherein the thickness of the cuprous oxide layer is 5-20 microns. The thickness of the wrapped cuprous oxide layer can be any value within a numerical range consisting of any two values of 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, and 20 microns.
[0024] A third aspect of the present invention provides an application of a foam copper composite three-dimensional current collector in a lithium battery.
[0025] A fourth aspect of the present invention provides a composite lithium metal negative electrode, wherein the composite lithium metal negative electrode comprises the above-mentioned foam copper composite three-dimensional current collector.
[0026] A fifth aspect of the present invention provides a lithium battery, wherein the lithium battery comprises the above-mentioned composite lithium metal negative electrode.
[0027] A sixth aspect of the present invention provides an electrical device, wherein the electrical device includes the above-mentioned lithium battery.
[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0029] Example 1
[0030] Preparation of FeF3 saturated solution: 200 mg of FeF3 was placed in a round-bottom flask, 100 mL of water was added, and the mixture was heated to 60°C and stirred under reflux for 5 h. After 5 hours, stirring was stopped, but heating was continued and the mixture was allowed to stand for 5 minutes. The supernatant was the FeF3 saturated solution at 60°C.
[0031] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.1 mol / L dilute hydrochloric acid solution for 6 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 60°C for 10 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times respectively, each time for 30 seconds, then put it into a vacuum drying oven at 60°C and dry it for 6 hours to obtain a foam copper composite three-dimensional current collector.
[0032] Example 2
[0033] The method of Example 1 was followed, except that the reaction temperature was 80° C. and the reaction time was 10 hours.
[0034] Example 3
[0035] The method of Example 1 was followed, except that the reaction temperature was 100° C. and the duration was 10 hours.
[0036] Example 4
[0037] The method of Example 1 was followed, except that the reaction temperature was 120° C. and the reaction time was 10 hours.
[0038] Commercial copper foam soaked in 0.1 mol / L dilute hydrochloric acid solution for 6 h was used as a comparison. The products of Examples 1-4 and the unreacted commercial copper foam were photographed with a digital camera, and scanning electron microscopy tests were performed at different magnifications to observe the overall and subtle surface structures of the copper foam. The results are as follows: Figure 1 As shown in the figure, the first row is commercial copper foam (denoted as CF) washed only with dilute hydrochloric acid, followed by photos of CF and SEM images at different magnifications, the second row is the product of the reaction of commercial copper foam with a saturated FeF3 solution at 60°C for 10 hours after the oxide layer is removed (denoted as CF-60), followed by photos of CF-60 and SEM images at different magnifications, the third row is the product of the reaction of commercial copper foam with a saturated FeF3 solution at 60°C for 10 hours after the oxide layer is removed (denoted as CF-80), the fourth row CF-100, the fifth row CF-120 and so on.
[0039] As can be seen from the digital photos, the surface of ordinary commercial copper foam CF is neat, showing a bright brick red color, without a cuprous oxide layer, and its SEM image shows a relatively regular network structure. At high resolution, the support of the network structure is relatively smooth. The color of CF-60 copper foam begins to darken, and it also shows a regular three-dimensional network structure in the SEM image. At high resolution, the surface of its three-dimensional network skeleton becomes rough, because it is covered with a thinner layer of cuprous oxide, but it is not uniform and dense enough. The color of the surface of CF-80 copper foam is darker, and its SEM image still shows a three-dimensional network structure. At high resolution, the surface of the three-dimensional skeleton is covered with a uniform and dense layer of cuprous oxide. CF-100 copper foam is dark red, indicating that the cuprous oxide layer on the surface is decomposed into copper oxide in small amounts, thereby deepening the surface color. However, its three-dimensional network structure remains unchanged. At high resolution, the surface of the three-dimensional skeleton is rough, and a thicker coating layer is generated. The CF-120 copper foam is red and black, indicating that the cuprous oxide layer on the surface is largely decomposed into cupric oxide. In the SEM spectrum, the three-dimensional network structure of the copper foam is still intact, indicating that only a coating layer is generated on the surface at different reaction temperatures, and the thickness of the coating layer is relatively thin. At high magnification, the coating layer on the surface of the three-dimensional network skeleton is transformed into a lamellar shape, indicating that the cuprous oxide on the surface is largely converted into cupric oxide.
[0040] Therefore, the preferred reaction temperature of the present inventors is 60-100°C.
[0041] Example 5
[0042] Preparation of FeF3 saturated solution: 200 mg of FeF3 was placed in a round-bottom flask, 100 mL of water was added, and the mixture was heated to 55°C and stirred under reflux for 5 h. After 5 hours, stirring was stopped, but heating was continued and the mixture was allowed to stand for 5 minutes. The supernatant was the FeF3 saturated solution at 55°C.
[0043] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.05 mol / L dilute hydrochloric acid solution for 7 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 100°C for 12 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times respectively, each time for 30 seconds, and then put it into a vacuum drying oven at 60°C for 10 hours to obtain a foam copper composite three-dimensional current collector.
[0044] The above current collector is used as the positive electrode and the metallic lithium is used as the negative electrode to assemble a button battery. The required amount of lithium metal is deposited on the foam copper according to the required amount of lithium metal. The foam copper is taken out and washed with DME solvent to obtain a composite lithium metal negative electrode. For example, the current density is 1 mA / cm2 , the deposition time is 10 hours, that is, 10 mAh / cm 2 composite lithium metal anode.
[0045] Example 6
[0046] Preparation of FeF3 saturated solution: 200 mg of FeF3 was placed in a round-bottom flask, 100 mL of water was added, and the mixture was heated to 80°C and stirred under reflux for 5 h. After 5 hours, stirring was stopped, but heating was continued. The mixture was allowed to stand for 5 minutes. The supernatant was the saturated FeF3 solution at 80°C.
[0047] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.05 mol / L dilute hydrochloric acid solution for 7 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 70°C for 8 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times, each time for 30 seconds, and then put it into a vacuum drying oven at 60°C for 8 hours to obtain a foam copper composite three-dimensional current collector.
[0048] The above current collector is used as the positive electrode and the metallic lithium is used as the negative electrode to assemble a button battery. The required amount of lithium metal is deposited on the foam copper according to the required amount of lithium metal. The foam copper is taken out and washed with DME solvent to obtain a composite lithium metal negative electrode. For example, the current density is 1 mA / cm 2 , the deposition time is 10 hours, that is, 10 mAh / cm 2 composite lithium metal anode.
[0049] Example 7
[0050] Preparation of FeF3 saturated solution: 200 mg of FeF3 was placed in a round-bottom flask, 100 mL of water was added, and the mixture was heated to 65°C and stirred under reflux for 5 h. After 5 hours, stirring was stopped, but heating was continued. The mixture was allowed to stand for 5 minutes. The supernatant was the saturated FeF3 solution at 65°C.
[0051] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.05 mol / L dilute hydrochloric acid solution for 8 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 80°C for 10 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times, each time for 30 seconds, and then put it into a vacuum drying oven at 60°C for 8 hours to obtain a foam copper composite three-dimensional current collector.
[0052] The above current collector is used as the positive electrode and the metallic lithium is used as the negative electrode to assemble a button battery. The required amount of lithium metal is deposited on the foam copper according to the required amount of lithium metal. The foam copper is taken out and washed with DME solvent to obtain a composite lithium metal negative electrode. For example, the current density is 1 mA / cm 2 , the deposition time is 10 hours, that is, 10 mAh / cm 2 composite lithium metal anode.
[0053] Example 8
[0054] Preparation of FeF3 saturated solution: 200 mg of FeF3 was placed in a round-bottom flask, 100 mL of water was added, and the mixture was heated to 60°C and stirred under reflux for 5 h. After 5 hours, stirring was stopped, but heating was continued. The mixture was allowed to stand for 5 minutes. The supernatant was the saturated FeF3 solution at 60°C.
[0055] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.05 mol / L dilute hydrochloric acid solution for 9 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 85°C for 9 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times each for 30 seconds, then put it into a vacuum drying oven at 60°C and dry it for 8 hours to obtain a foam copper composite three-dimensional current collector.
[0056] The above current collector is used as the positive electrode and the metallic lithium is used as the negative electrode to assemble a button battery. The required amount of lithium metal is deposited on the foam copper according to the required amount of lithium metal. The foam copper is taken out and washed with DME solvent to obtain a composite lithium metal negative electrode. For example, the current density is 1 mA / cm 2 , the deposition time is 10 hours, that is, 10 mAh / cm 2 composite lithium metal anode.
[0057] Example 9
[0058] Preparation of FeF3 saturated solution: Take 200 mg of FeF3 and put it into a round-bottom flask, add 100 mL of water, heat to 60℃, stir and reflux for 5 hours, stop stirring after 5 hours, continue heating, and let it stand for five minutes. The supernatant is the FeF3 saturated solution at 60℃.
[0059] Preparation of foam copper composite three-dimensional current collector: soak commercial foam copper in 0.1 mol / L dilute hydrochloric acid solution for 10 hours to remove the oxide layer on the surface, then cut it into 1 cm×2 cm sheets and put it into a 25 mL polytetrafluoroethylene-lined reactor, take 10 mL of FeF3 saturated solution and put it into the above reactor containing foam copper, then put it into a forced air drying oven and heat it to 80°C for 10 hours, cool it to room temperature, take out the foam copper with tweezers, rinse it with water and ethanol three times respectively, each time for 30 seconds, then put it into a vacuum drying oven at 60°C and dry it for 6 hours to obtain a foam copper composite three-dimensional current collector.
[0060] The above current collector is used as the positive electrode and the metallic lithium is used as the negative electrode to assemble a button battery. The required amount of lithium metal is deposited on the foam copper according to the required amount of lithium metal. The foam copper is taken out and washed with DME solvent to obtain a composite lithium metal negative electrode. For example, the current density is 1 mA / cm 2 , the deposition time is 10 hours, that is, 10 mAh / cm 2 composite lithium metal anode.
[0061] Example 10
[0062] The preparation of FeF3 saturated solution is the same as in Example 9.
[0063] The commercial copper foam was immersed in a 0.1 mol / L dilute hydrochloric acid solution for 7 hours to remove the oxide layer on the surface, and then cut into 1 cm × 2 cm sheets and placed in a 25 mL polytetrafluoroethylene-lined reactor. 10 mL of FeF3 saturated solution was placed in the reactor containing the copper foam, and then placed in a forced air drying oven and heated at 80 ° C for 10 hours. After cooling to room temperature, the copper foam was taken out with tweezers and rinsed with water and ethanol three times for 30 seconds each time, and then placed in a vacuum drying oven at 60 ° C for 10 hours to obtain a copper foam composite three-dimensional current collector.
[0064] The above-mentioned copper foam composite current collector is placed in molten lithium (400°C) until the silvery white lithium completely covers the surface of the copper foam current collector (about 1-2 minutes), then it is taken out and placed at room temperature to obtain a composite lithium metal negative electrode.
[0065] The thickness of the cuprous oxide layer in the current collector prepared in the above Examples 5-10 is 5-20 microns.
[0066] The coulombic efficiency of the CF-80 prepared in Example 9 as the current collector is compared with that of the unmodified foam copper CF. The results are as follows: Figure 2 shown.
[0067] As can be seen from the figure, the first-week coulombic efficiency of CF is only 41%, while the first-week coulombic efficiency of CF-80 prepared by the present invention is as high as 90.5%. In the subsequent charge and discharge cycle process, CF-80 maintains a relatively stable coulombic efficiency, while the coulombic efficiency of CF fluctuates greatly. This is due to the coating of the lithium-philic substance Cu2O on the surface of CF-80. Cu2O can significantly reduce the overvoltage of lithium nucleation, reduce the resistance of lithium nucleation, and induce uniform deposition of lithium. The lithium-philic substance can often cause lithium to be deposited in a planar manner. The lithium deposition is relatively dense. The deposited lithium is relatively dense and can reduce the side reaction with the electrolyte. The lithium deposition is planar and dense, and SEI can often exist stably and can also inhibit the occurrence of side reactions. Therefore, the deposited lithium can be more stripped, the coulombic efficiency is higher, the SEI is stable and not broken, and the coulombic efficiency is relatively stable.
[0068] CF itself is not lithium-philic, the nucleation overvoltage of lithium is large, the lithium nucleation resistance is large, the nucleation site is relatively isolated, and the subsequent deposition often continues to deposit at the original nucleation site, resulting in the growth of lithium dendrites. Lithium dendrites have a large specific surface area and high activity, which can produce more serious side reactions with the electrolyte. When lithium is stripped, the dendrite lithium often strips off from the root, causing the dendrite lithium to break. The broken part reacts with the electrolyte to form SEI, which causes the broken lithium to be unable to transfer electrons, lose activity and become dead lithium, resulting in low coulomb efficiency.
[0069] The prepared CF-80 current collector was used as the negative electrode and commercial lithium was used as the negative electrode to assemble full batteries with NCM-811. Their cycling performances are shown in Figure 3 As shown, the first-week discharge capacity of NCM / / CF-80 / Li is 155.6mAh / g, and it remains at 132.7mAh / g after 150 cycles. In contrast, the first-week discharge capacity of the NCM / Li battery is 153.7mAh / g, and it is 122.2mAh / g after 150 cycles. Compared with the full battery provided by the present invention, the cycle stability is poor. The difference in their cycle performance may be caused by the different metal lithium negative electrodes. The metal lithium loaded by CF-80 is stripped and deposited in an orderly manner each time, the SEI on the surface is stable, there are fewer side reactions, and the internal impedance of the battery changes slightly, so it can still maintain a high capacity after multiple cycles.
[0070] The commercial lithium foil matched with NCM-811 has a faster capacity decay. This may be because the lithium deposition at the negative electrode is often uneven, the stacking is relatively loose, and dendrite lithium may be formed. The above lithium has a larger exposed specific surface area and more side reactions with the electrolyte, resulting in increased impedance. In addition, the uneven deposition of lithium often leads to large changes in the morphology of the deposited lithium, which can easily lead to the rupture of the formed SEI, which in turn aggravates the side reactions with the electrolyte and further increases the battery impedance, resulting in increased polarization and faster capacity decay.
[0071] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a foam copper composite three-dimensional current collector, characterized in that: The copper foam is immersed in FeF3 solution to obtain a copper foam composite three-dimensional current collector with a cuprous oxide layer coated on the surface.
2. The preparation method according to claim 1, characterized in that: The FeF3 solution is a saturated FeF3 solution; preferably, the saturated FeF3 solution is a saturated solution at 55-80°C, preferably a saturated solution at 55-65°C.
3. The preparation method according to claim 1 or 2, characterized in that: The immersion process comprises: reacting at a temperature of 60-100° C. for 8-12 hours, cooling to room temperature, taking out the foam copper, washing and drying, and obtaining the foam copper composite three-dimensional current collector with a cuprous oxide layer wrapped on the surface; Preferably, the immersion process comprises: reacting at a temperature of 70-90° C. for 8-10 hours.
4. The preparation method according to claim 3, characterized in that: The preparation method further comprises: before the reaction, soaking the foam copper in dilute hydrochloric acid to remove the oxide layer on its surface, wherein the concentration of the dilute hydrochloric acid is 0.05-0.2 mol / L and the soaking time is not less than 6 hours.
5. A foam copper composite three-dimensional current collector obtained by the preparation method according to any one of claims 1 to 4.
6. The foam copper composite three-dimensional current collector according to claim 5, characterized in that: The copper foam composite three-dimensional current collector comprises copper foam and a cuprous oxide layer wrapped on the surface of the copper foam, wherein the thickness of the cuprous oxide layer is 5-20 microns.
7. Use of the foam copper composite three-dimensional current collector according to claim 5 or 6 in a lithium battery.
8. A composite lithium metal negative electrode, characterized in that The composite lithium metal negative electrode comprises the foam copper composite three-dimensional current collector according to claim 5 or 6.
9. A lithium battery, characterized in that: The lithium battery comprises the composite lithium metal negative electrode according to claim 8.
10. An electrical device, characterized in that: The electrical equipment comprises the lithium battery according to claim 9.